The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-665259/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FCER1G Positively Relates To Macrophage Infiltration In Clear Cell Renal Cell Carcinoma And Contributes To Unfavorable Prognosis By Regulating Tumor Immunity

Abstract: Background: Tumor-associated macrophages (TAMs) are closely related to unfavorable prognosis of patients with clear cell renal cell carcinoma (ccRCC). However, the important molecules in the interaction between ccRCC and TAMs are unclear.Methods: TCGA-KIRC gene expression data of tumor tissues and normal tissues adjacent to tumor were compared to identify differentially expressed genes in ccRCC. TAMs related genes were discovered by analyzing the correlation between these differentially expressed genes and com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…In addition, M2 macrophages can acquire their tumor suppressor function in part by suppressing cytotoxic T cells. Tis may explain the relevance of FCER1G to macrophage and T cell function [31]. Tese fndings were consistent with our results that high expression of FCER1G was positively correlated with infltration of M2 macrophages and negatively correlated with CD8 T cells.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, M2 macrophages can acquire their tumor suppressor function in part by suppressing cytotoxic T cells. Tis may explain the relevance of FCER1G to macrophage and T cell function [31]. Tese fndings were consistent with our results that high expression of FCER1G was positively correlated with infltration of M2 macrophages and negatively correlated with CD8 T cells.…”
Section: Discussionsupporting
confidence: 90%
“…TAMs have been shown to contribute to tumor development through a variety of mechanisms. In addition, TAMs are considered to reflect clinical outcome in ccRCC [50,51]. In this work, we also found that the expression of TLR4 is widely associated with the extent of macrophage infiltration (Figure 6C).…”
Section: Discussionsupporting
confidence: 59%